THE INFLUENCE OF THE MARKETING MIX ON BRAND IMAGE IN THE COMMUNITY(Case Study at Bank Bjb Main Branch) - Dendi Nugraha; Sri Rochani Mulyani; Zaenal Aripin (PT. Kreatif Indonesia Satu, 2024)
Purpose .of .This .Research .Is .To .Know .How . The Effect of Marketing Mix on Brand Image in the Community (Case Study at Bank Bjb Main Branch). The .method.used.is.descriptive.research.which.analyzes.the.results.of.research.but.is.not.used.to.draw.broader.conclusions. So .here .we have .independent .variables .and .dependent .variables.. The data collection technique used is a field study with a questionnaire to 100 respondents and library research. Based on the author's research, it can be seen that the relationship between marketing mix and brand image in the community (case study at bank bjb main branch). . Meanwhile, based on statistical calculations carried out with SPSS, obtained . known value F = 243.617, and value Sig. = 0.000, while value F table with df (7.92) = 2.11. Thus H0 is rejected, H8 is accepted, these variables Product (X1), Price (X2), Place (X3), Promotion (X4), People (X5), Process (X6), Physical Evidence (X7), together have a significant effect on Brand Image (Y). Thus H0 is rejected, and H8 is accepted, these variable variables Product (X1), Price (X2), Place (X3), Promotion (X4), People (X5), Process (X6), Physical Evidence (X7), together have a significant effect on the variable Brand Image (Y).